(untitled) (OODBODHAN, 2024)
Steels have microstructures such as ferrite, pearlite, and martensite, which directly influence properties like hardness, strength, and thermal conductivity. The impact of specific heat treatment procedures on mild steel and TMT bars, such as normalizing and quenching in mediums like water, ice, and oil, lead to changes in these microstructures, resulting in variations in mechanical and thermal properties. Nital reagent used for etching steel and other ferrous materials reveals their microstructures. Optical microscopy and image analysis technique is particularly effective in determining the amount or composition of different phases within a heat treated sample. Ice quenching is one that has the maximum (i.e., 85.05) percent of martensite in a mild steel rod, which signifies higher hardness making it suitable for applications where high strength is critical but, ductility is less important. Similarly, water quenched Thermex TMT bar shows a maximum (i.e., 11.73) percent of ferrite, which shows higher ductility as compared with mild steel rod and other TMT rods that makes it better for applications where deformation occurs, whereas normalizing in mild steel results in 73.37% of pearlite which suggests good balance between strength and ductility making it suitable for components that undergo cyclic loading. The conclusion shows the relevance of looking for the proper heat treatment techniques in order to obtain the best mechanical properties for various steels used in wide range of applications.